Rural regional governance in the United States: the case of the Resource Conservation and Development Program - Lu, Max; Jacobs, John C. (My University, 2013)
Rural governance has drawn considerable attention from both local government officials and scholars in the United States since the early 1990s. It is touted as a way to mitigate the limitations of the traditional government unit-based approaches to problem solving and decision making and to foster partnerships across both jurisdictional boundaries and sectors (public, private, and nonprofit). Established in 1962, the Resource Conservation and Development (RC&D) program of the U.S. Department of Agriculture provides a unique model of rural regional governance. Acting as a coalition of governments, private businesses, individuals, and interest groups, the RC&D program provides the flexibility needed to deal with issues at the appropriate spatial scale. It incorporates aspects of both grassroots and governmental organizations and can bring together local interests and expertise with governmental policy and support in service provision, problem solving, and economic development. The approach does not necessarily entail loss of power on the part of the state, but it does provide a mechanism for local people to exercise their agency, to tackle their problems, and to decide which elements of their lives they want to sustain.
Keywords: Governance; Resource Conservation and Development program; Rural development